Triiodothyronine mimics the effects of estrogen in breast cancer cell lines - Nogueira, C. R.; Brentani, M. M. (Elsevier B.V., 1996)
MCF-7 (estrogen receptor positive - ER(+)) and MDA-MB-231 (estrogen receptor negative - ER(-)) are human breast cancer cell lines which express functional thyroid hormone receptors (c-erb A alpha 1 and c-erb beta 1) as indicated by stimulation of mitochondrial alpha-glycerophosphate dehydrogenase. In MCF-7, mimicking E(2), T-3 stimulated growth in a dose-dependent (10(10) M-10(-8) M) manner, induced the expression of progesterone receptor and growth factor TGF alpha mRNAs and inhibited that of TGF beta mRNA; T-3 also increased progesterone binding and LDH5 isozyme activities. None of these effects were observed in (ER(-)) MDA-MB-231 cells. 10(-6) M tamoxifen (TAM) reverted growth stimulation, suppressed progesterone receptor and TGF alpha mRNA induction and restored TGF beta mRNA to control levels in T-3-treated MCF-7 cells. That T-3 is acting in MCF-7 cells via its binding to ER is suggested by the immunoprecipitation of pre-bound I-125-T-3 from MCF-7 nuclear extracts by an ER-specific monoclonal antibody and by the displacement of H-3-estradiol binding to ER by radioinert T-3. Copyright (C) 1996 Elsevier B.V. Ltd.